Experiences of adolescent boys with absent fathers in single-mother families in Bakenberg Village, Limpopo Province - Phasha, Kgethego Terrance (My University, 2021)
The phenomenon of absent fathers continues to be one of the major social problems which affect families globally. This study has examined the experiences of adolescent boys who grow up without fathers in single-mother families in Bakenberg village in Limpopo Province. The objectives of this study were to establish the experiences of adolescent boys with absent fathers, to describe the challenges faced by adolescent boys in growing up without a father and to determine their understanding of the role and value of having a father. A qualitative approach was used for this study. This approach was complemented by the use of a descriptive phenomenological research design for its focus on lived human experiences and the meanings participants assigned to those experiences. A purposive sampling technique was used to collect data from 18 adolescent boys through face-to-face interviews and as well as focus group discussions. The data collected was analysed using the thematic analysis method. The findings of this study showed that participants regarded fathers as an important figure in their lives and their families and his absence brought about financial challenges, poor academic progress, indulgence in alcohol and smoking brought about by negative outside influences as well as lack of immediate gender role model. The study also revealed that in the absence of fathers, these boys end up being compelled to play the role of the man in their families. For the participants in this study, other male figures such as uncles and grandfathers played a vital role in as far as gender specific roles and identity development is concerned. The study encourages more research into issues that impact negatively the children in one-parent families. The study also draws attention to the necessity to discover the reasons for the disintegration of the family structure, thereby highlighting a serious national and global problem which needs to be addressed for the health and well-being of our people because families form the foundation of a country‟s citizenry.
Thesis (M. A. (Social Work)) -- University of Limpopo, 2021
Keywords: Adolescent boys; Absent fathers; Single-mother families; Bakenberg Village; Limpopo Province; Teenage boys -- Social conditions; Minority teenagers -- Social conditions; Adolescent psychology; Absentee fathers -- South Africa -- Statistics; Single mothers -- South Africa